From the rector's desk - Hamali, Jamil (UiTM Sarawak, 2021)
First and foremost, I would like to take this opportunity to wish all of you a happy new year 2021. With 2021 being the Year ofExcellence for UiTM going along the theme “Pecutan ke Arah Kecemerlangan”, UiTM is embarking on a journey towards becoming a globally-renowned university. In his Amanat Naib Cancelor 2021, Vice Chancellor ofUiTM, Yang Berbahagia Professor Emeritus Datuk Ir. Dr. Mohd Azraai Kassim stressed the importance ofquality education, global excellence and values-based performance as the key elements towards becoming a globally-renowned university. In this regard, UiTM Sarawak is on track in its vision to be one ofthe top ifnot the top institution ofhigher learning in Borneo. Although 2020 hasleft us for good, the challenges we faced and the valuable experiences gained from the Covid-19 global pandemic should give us greater confidence to face the uncertainties that lie ahead. We must move forward and brace ourselves for new, exciting challenges with the hope that we can achieve more when the Covid-19 pandemic is over.